International Anemia Prevalence and Management in Peritoneal Dialysis Patients. Issue 6 (November 2019) - Perlman, Rachel L.; Zhao, Junhui; Fuller, Douglas S.; Bieber, Brian; Li, Yun; Pisoni, Ronald L.; Robinson, Bruce M.; Johnson, David W.; Kawanishi, Hideki; Davies, Simon J.; Schreiber, Martin J.; Perl, Jeffrey
Background: The optimal treatment for managing anemia in peritoneal dialysis (PD) patients and best clinical practices are not completely understood. We sought to characterize international variations in anemia measures and management among PD patients. Methods: The Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS) enrolled adult PD patients from 6 countries from 2014 to 2017. Hemoglobin (Hb), ferritin levels, and transferrin saturation (TSAT), as well as erythropoiesis stimulating agents (ESAs) and iron use were compared cross-sectionally at study enrollment in Australia and New Zealand (A/NZ), Canada, Japan, the United Kingdom (UK), and the United States (US). Results: Among 3, 603 PD patients from 193 facilities, mean Hb ranged from 11.0 – 11.3 g/dL across countries. The majority of patients (range 53% – 59%) had Hb 10 – 11.9 g/dL, with 4% – 12% patients ≥ 13 g/dL and 16% – 23% < 10 g/dL. Use of ESAs was higher in Japan (94% of patients) than elsewhere (66% – 79% of patients). In the US, 63% of patients had a ferritin level > 500 ng/mL, compared with 5% – 38% in other countries. In the US and Japan, 87% – 89% of PD patients had TSAT ≥ 20%, compared with 73% – 76% in other countries. Intravenous (IV) iron use within 4 months of enrollment was higher in the US (55% of patients) than elsewhere (6% – 17% patients). Conclusions: In this largest international observational study of anemia and anemia management in patients receiving PD, comparable Hb levels across countries were observed but with notable differences in ESA and iron use. Peritoneal dialysis patients in the US have higher ferritin levels and higher IV iron use than other countries.